Characterisation of Recombinant Human Erythropoietin Obtained from CHOpE—Erythropoietin Producing Strain of Chinese Hamster Ovary Cells - I. F. Radaeva; V. A. Ternovoy; A. O. Sementsova; N. B. Dumchenko; E. A. Nechaeva (Биопрепараты: Профилактика, диагностика, лечение)
Development and implementation in clinical practice of recombinant human erythropoietins (rhEPOs) remain a priority task today. Additional studies were performed in order to obtain clinical trial authorisation for rhEPO tablets for oral use. The studies were aimed to demonstrate the suitability of the erythropoietin producer strain based on Chinese hamster ovary cells (CHOpE) for the production of rhEPO, and the compliance of the substance characteristics with the requirements for erythropoietin (EPO).The aim of the study was to characterise the rhEPO substance obtained from the CHOpE strain cells in accordance with the requirements for EPO.Materials and methods: the rhEPO substance was obtained by culturing the strain of Chinese hamster ovary cells—CHOpE. The expression construct of the producer strain was evaluated using methods for determination of nucleotide and amino acid sequences. The Sanger method was used to perform sequencing of the nucleotide sequence encoding the human EPO gene. The amino acid sequences of the rhEPO molecule C- and N-termini were determined by the Edman method. The copy number of the EPO gene in CHOpE cells was determined by real-time polymerase chain reaction. The properties of the rhEPO substance were evaluated in accordance with the requirements for EPO. Isoelectric focusing, peptide mapping, and polyacrylamide gel electrophoresis were used for identification of the rhEPO substance. The ratio of isoform composition was determined by capillary electrophoresis. Dimer impurities and high molecular weight related substances were determined by high-pressure liquid chromatography. The content of protein and residual nucleic acids was determined by spectrophotometry. The concentration of the rhEPO substance was assessed by enzyme immunoassay.The results of the study confirmed genetic stability of the CHOpE producer strain and demonstrated identity of N- and C-terminal amino acid sequences of the rhEPO molecule to those of the natural EPO. The CHOpE producer strain was used to obtain a rhEPO substance which is homogenous and does not contain impurities of EPO oligomeric forms. Dimers and high molecular weight related substances account for less than 0.5%. The rhEPO molecular weight ranges from 32 to 38 kDa, and the isoelectric point is within 2.8—4.15. The study identified the peaks of isoforms 1–8, the isoform composition of the rhEPO substance corresponds to that of EPO. It was determined that 1 mol of the substance contains 13.75 mols of sialic acids.Conclusions: the study confirmed the suitability of the CHOpE producer strain for the production of rhEPO. The obtained rhEPO substance meets requirements for EPO.